"Day's Residues": One Vertex Among Many. (August 2022) - Taiana, Cecilia
The post-Bionian paradigm in psychoanalysis invites us to listen to the session as a waking-dream-thought where unconscious-thinking-in progress is continuous. The hypothesis put forward here and illustrated using clinical material is that we can use the notion of day's residues as a metaphor to refer to the incoming narrative of the patient. Whatever the patient brings to the session can be conceived as "day's residues" in that they are potential instigators of waking-dream-thought in the session. This metaphor helps the analyst place brackets around the outside of the session, deconcretizing what apparently are hard facts, so that immediate contact is made to create a shared perspective, possibly producing in this session "food" for the mind. To create the waking-dream-thought of the session, the analyst may consider listening to the incoming narrative as a metaphor. This is not a new or different concept but a particular kind of elaboration on the metaphoric stance taken by psychoanalysts of all stripes; it is an elaboration that expands the ways we can describe the session and narrow the gap between talking about the session and the experience of the session itself.